2010
DOI: 10.1519/jsc.0b013e3181ddb207
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rest Interval Lengths on Hypotensive Response After Strength Training Sessions Performed by Older Men

Abstract: The purpose of this study was to compare the postexercise hypotensive response after different rest intervals between sets (1 and 2 minutes) in normotense older men. Seventeen older men (67.6 ± 2.2 years) with at least 1 year of strength training experience participated. After determination of 10 repetition maximum (10RM) loads for exercises, subjects performed 2 different strength training sessions. On the first day, volunteers performed 3 sets of 10 repetitions per exercise at 70% 10RM, with 1 or 2 minutes' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
18
2
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 19 publications
6
18
2
9
Order By: Relevance
“…Previous studies observed similar cardiovascular responses after resistance exercise with rest intervals between 1 and 3 minutes (DE SALLES et al, 2010;VELOSO et al, 2010). Because some studies have suggested that metabolite-induced vasodilation might affect the post-exercise hypotension mediated by nitric oxide (LIZARDO et al, 2008), in the current study we expected that a very short rest interval (30 sec) could potentiate post-exercise hypotension.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies observed similar cardiovascular responses after resistance exercise with rest intervals between 1 and 3 minutes (DE SALLES et al, 2010;VELOSO et al, 2010). Because some studies have suggested that metabolite-induced vasodilation might affect the post-exercise hypotension mediated by nitric oxide (LIZARDO et al, 2008), in the current study we expected that a very short rest interval (30 sec) could potentiate post-exercise hypotension.…”
Section: Discussionsupporting
confidence: 56%
“…To date, only two studies have analyzed the effect of the inter-set rest interval on cardiovascular response after resistance exercise. In both studies, the cardiovascular response after resistance exercise was independent of the rest interval adopted (DE SALLES et al, 2010;VELOSO et al, 2010). However, neither employed rest intervals shorter than 1 minute, which is known to promote greater metabolite accumulation (RATAMESS et al, 2007;TAKARADA;ISHII, 2002).…”
mentioning
confidence: 99%
“…Among these training variables, evidence has suggested that the rest interval between sets affects various acute responses including metabolic (4,5), hormonal (6-9), cardiovascular (10)(11)(12), neuromuscular and perceived ratings of exertion (13,14). Thus, the rest interval between sets can be considered a key variable for resistance training prescription, since it affects distinct acute responses, which in turn could modulate chronic neuromuscular adaptations (8,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Somente a partir da década de 1980 iniciou-se sistematicamente a investigação desse fenômeno, relacionando-o como efeito clínico relevante (PESCATELLO et al, 1991). Alguns estudos identificaram a HPE em normotensos, porém com menor magnitude quando comparados a hipertensos (FORJAZ et al, 2000;BERMUDES et al, 2003;DE SALLES et al, 2010). Em indivíduos jovens e normotensos, reduções médias de 8 a 10 mmHg são observadas na pressão arterial sistólica (PAS) por algumas horas pós-exercício (MACDONALD, 2002).…”
Section: Introductionunclassified